Political economy of communications in india the good, the bad and the ugly - "Thomas, Pradip Ninan" (New Delhi, 2010)
This book is a critical study of the political economy of communications in India. It explores the ways in which contexts, structures, policies and processes at national and international levels shape media structures and explores how a political economy-inspired approach can be used to understand both media dominance and resistance. It deals with a variety of issues that are key to understanding the political economy of communication$1 (Bfrom intellectual property to audio-visual trade and media ownership, liberalisation, privatisation, and media politics.s
Keywords: Mass media-Economic aspects-India